PENGARUH PROMOSI PENJUALAN TERHADAP PENINGKATAN MINAT BELI KONSUMEN PADA KAFE TERAKOTA 114 DI BEKASI - Tasya Celometa Anastasia; Tieska Syaharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the effect of sales promotion on consumer purchase intention at Caffe Terokota 114 which opened in July 2024. Sales promotions, including discounts, bundling packages, and loyalty programs, were used to attract new customers and increase repeat visits. The research method employed was a quantitative approach with a survey design. Data were collected through questionnaires distributed to 100 respondents, who were customers of the café. Data analysis was conducted using simple linear regression to measure the relationship between sales promotion and consumer purchase intention. The results showed that sales promotions had a significant positive effect on increasing consumer purchase intention, with a regression coefficient of 0.68 (p < 0.05), indicating that sales promotion contributed positively to consumer purchase intention. These findings emphasize the important role of sales promotions in attracting consumer attention, especially for new businesses still establishing brand awareness. This research is expected to provide insights for café managers and other culinary business owners in designing effective marketing strategies.